Executive functions predict conceptual learning of science. (11th January 2016) - Rhodes, Sinéad M.; Booth, Josephine N.; Palmer, Lorna Elise; Blythe, Richard A.; Delibegovic, Mirela; Wheate, Nial J.
Abstract : We examined the relationship between executive functions and both factual and conceptual learning of science, specifically chemistry, in early adolescence. Sixty‐three pupils in their second year of secondary school (aged 12–13 years) participated. Pupils completed tasks of working memory (Spatial Working Memory), inhibition (Stop‐Signal), attention set‐shifting (ID/ED), and planning (Stockings of Cambridge), from the CANTAB. They also participated in a chemistry teaching session, practical, and assessment on the topic of acids and alkalis designed specifically for this study. Executive function data were related to (1) the chemistry assessment which included aspects of factual and conceptual learning and (2) a recent school science exam. Correlational analyses between executive functions and both the chemistry assessment and science grades revealed that science achievements were significantly correlated with working memory. Linear regression analysis revealed that visuospatial working memory ability was predictive of chemistry performance. Interestingly, this relationship was observed solely in relation to the conceptual learning condition of the assessment highlighting the role of executive functions in understanding and applying knowledge about what is learned within science teaching.